ESP TEXTBOOK EVALUATION: English for Islamic Learning for College Students - Lalu Suhirman (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
ESP Textbook evaluation has become a necessary practice in the field of teaching, seeking to assist in the choice of the best suitable textbook for a specific context. This article  presents an evaluation of English textbook “English for Islamic Learning: for College Students”.The researcher identifies how well the textbook meets the students' English learning needs and how much appropriate activities  it is presented.The ESP textbook has been evaluated impressionistically which covers the textbook (contents, presentations, and strategies)  and student’s needs and interests.For this purpose, 20 students and 1 teacher were selected and data were gathered by two questionnaires which were made by Garant (1987). The teacher questionnaire consisted of 10 items and the student version is also consisted of 10 items. An additional component of the study consisted of a student “needs analysis” that was conducted at the same time as the textbook evaluation survey. After analyzing data, it was shown that although the textbook had some drawbacks, especially in terms of language skills,  it had met students’ needs and interests.